Penyuluhan dan Pengarahan Mengenai Parenting Pattern yang Tepat dalam Peningkatan Self-Efficacy Anak Usia Sekolah - Hilda Mazarina Devi; Ronasari Mahaji Putri (Jurnal Pemberdayaan Masyarakat, 2022)
Low self-efficacy may influence on anxiety and avoidance behavior among school-aged children. Proper parenting style from parents is needed to prevent these negative events to be occured. This social service program was carried out through counseling and simulation about parenting styles to increase the children's self-efficacy. Through discussions with parents, training and simulation it is hoped that parents will be able to open up their knowledge about children's self-efficacy. There are differences in understanding parenting patterns and self-efficacy before and after the program delivered.